Assessing the Impact of Rising Temperatures and Rainfall Variability on Tomato Production in Kirkuk Governorate: An Observational Analysis (2010–2024) - Mohammed, Azheen Othman (American Journal of Biology and Natural Sciences, 2025)
This research paper will look at the impacts of climatic changes to tomato farming in Kirkuk Governorate between the years 2010 and 2024. Evaluation of climatic data gathered by NASA POWER, NOAA, and World Clim shows a definite warming pattern, especially in the maximum temperature, and big variation in the yearly precipitation. The data on tomato production indicate that there is significant variability in the outcome of year to year, with high yield decline being reported in years of high heat stress. Correlation and regression analysis reveal maximum temperature as the most significant climatic factor that has negative impact on tomato yield, but rainfall has the less impact because of the common use of irrigation systems. The results indicate how open field tomato farming is vulnerable in the semi-arid areas like Kirkuk, where summer temperatures exceed the physiological tolerance levels of the crop. The research finds that the main solutions to increase the resilience and maintain tomato yield in the face of the current climate change are the use of heat-tolerant varieties, the efficiency of irrigation, and the expansion of the use of the systems of the protected cultivation.